Exploratory Study of the Brain Response in Facial Synkinesis after Bell Palsy with Systematic Review and Meta-analysis of the Literature - Krane, N.A.; Loyo, M.; Pollock, J.; Hill, M.; Johnson, C.Z.; Stevens, A.A. (American Journal of Neuroradiology, 2022)
BACKGROUND: Facial synkinesis, characterized by unintentional facial movements paired with intentional movements, is a debilitating sequela of Bell palsy.PURPOSE: Our aim was to determine whether persistent peripheral nerve changes arising from Bell palsy result in persistent altered brain function in motor pathways in synkinesis.DATA SOURCES: A literature search using terms related to facial paralysis, Bell palsy, synkinesis, and fMRI through May 2021 was conducted in MEDLINE and EMBASE. Additionally, an fMRI study examined lip and eyeblink movements in 2 groups: individuals who fully recovered following Bell palsy and individuals who developed synkinesis.STUDY SELECTION: Task-based data of the whole brain that required lip movements in healthy controls were extracted from 7 publications. Three studies contributed similar whole-brain analyses in acute Bell palsy.DATA ANALYSIS: The meta-analysis of fMRI in healthy control and Bell palsy groups determined common clusters of activation within each group using activation likelihood estimates. A separate fMRI study used multivariate general linear modeling to identify changes associated with synkinesis in smiling and blinking tasks.DATA SYNTHESIS: A region of the precentral gyrus contralateral to the paretic side of the face was hypoactive in synkinesis during lip movements compared with controls. This region was centered in a cluster of activation identified in the meta-analysis of the healthy controls but absent from individuals with Bell palsy.LIMITATIONS: The meta-analysis relied on a small set of studies. The small sample of subjects with synkinesis limited the power of the fMRI analysis.CONCLUSIONS: Premotor pathways show persistent functional changes in synkinesis first identifiable in acute Bell palsy.ALEactivation likelihood estimateBLINKeye blinkingBPBell palsyHChealthy controlsPoCpostcentral gyrusPrCprecentral gyrusSMILEsmilingRESTrest blocks